The Cosmic Rays Interaction with the Atmosphere and Estimation of the Number of Primary Particles in the Emission of Cherenkov - Lazem, Taha Hussein (Technium: Romanian Journal of Applied Sciences and Technology, 2026)
In the range from (1014-1016) electronvolts (eV), this research hopes to determine the number of charged particles (N) as a function of the energy of the main particle. 〖(E〗_o)The maximum depth of the Extensive Air Shower (EAS), Xmax, is also determined for electromagnetic and hadronic cascades in the same energy range. The inelasticity parameter's (k) role in describing neutrino counts as they fluctuate. The major objective is to evaluate the potential for determining the particles responsible for these showers and their energies around the cosmic ray (CR) spectrum's bend point for different fundamental particles (iron nuclei, proton, lithium, Helium) and at different zenith angles. This research looks at the production of Wide Air Showers and the emission of Cherenkov photons because of the collision of primary cosmic ray particles with atmospheric nuclei. As a function of the original energy 〖(E〗_o) between (1014-1016) eV, the expected number of charged particles can be calculated. The maximum depth of shower growth (Xmax) is computed for electromagnetic and hadronic chains, and the longitudinal evolutions of Extensive Air Showers are analyzed. We characterize inelasticity and its effect on neutrino generation using the parameter (k). In order to verify the results, researchers compare the Tunka-25 Tunka-133 vast air shower array facility's observations with their personalized calculations of the Cherenkov light Detection Function (LDF).